From Myths of Victimhood to Fantasies of Violence: How Far-Right Narratives of Imperilment Work - Marcks, Holger (Terrorism and political violence, 2022)
Why is far-right rhetoric so dangerous? In recent years, scholars and policy makers alike have striven to unpack the black box of extremists’ online communication and the rise of far-right violence. Particularly the role of social media in spreading hate speech and fostering radicalization has caught a lot of attention; however, there has been little success in pinning down the drivers of violence. Drawing on the concept of dangerous speech, we take a step back from the violent effects of far-right online communication. Instead, we examine its logical functioning to illuminate the upstream processes that constitute hate and legitimize violence. More concretely, we study how far-right narratives employed on social media mobilize emotions that prepare for the acceptance or even use of violence. Analyzing the argumentative structures of two anti-immigration campaigns in Germany, we find a network of narratives where narratives of imperilment— supported by narratives of conspiracy and inequality—converge into a greater story of national threat and awakening. By constructing a situation of collective self-defense, violence becomes a logical option, even if violent action is not explicitly proposed. Counter-narrative efforts should thus not only focus on hate speech but also address the myths of victimhood, which are constitutive of (violent) palingenetic fantasies.